High-heat-resistance low-dielectric multi-aromatic-ring phosphorus-containing phenolic aldehyde curing agent, preparation method thereof, composition for copper-clad plate and application of composition

By designing a high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent and adopting a specific preparation method, the problems of insufficient heat resistance and low purity of phosphorus-containing phenolic curing agent in the prior art are solved, and good dielectric, heat resistance, flame retardant and toughness of copper clad plates are achieved.

CN119735615AActive Publication Date: 2025-04-01SICHUAN DONGFANG INSULATING MATERIAL +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411852937.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

In the prior art, the use of phosphorus-containing phenolic curing agent in copper clad plates has problems such as insufficient heat resistance and low purity to adverse dielectric performance, making it difficult to meet the demand for high-performance copper clad plates.

Method used

By designing a high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent, including naphthalene ring structure, bisphenol structure, benzene ring structure with large volume side chains, and phosphorus structure, and using specific preparation methods, including hydroxymethylation reaction, neutralization reaction, etherification reaction and deethanol reaction, the purity and performance of the curing agent are improved.

Benefits of technology

The prepared copper clad plate has good dielectric properties, heat resistance, flame retardant properties and toughness, dielectric constant ≤3.86, dielectric loss ≤0.0078, glass transition temperature ≥185℃, and flame retardant performance reaches the UL94 V-0 level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191046790000021
    Figure BDA0005191046790000021
  • Figure BDA0005191046790000031
    Figure BDA0005191046790000031
  • Figure BDA0005191046790000034
    Figure BDA0005191046790000034
Patent Text Reader

Abstract

The invention discloses a high-heat-resistance low-dielectric multi-aromatic-ring phosphorus-containing phenolic aldehyde curing agent, a preparation method thereof, a composition for a copper-clad plate and application of the composition, and belongs to the technical field of electronic resin synthesis. The high-heat-resistance low-dielectric multi-aromatic-ring phosphorus-containing phenolic aldehyde curing agent comprises a naphthalene ring structure, a bisphenol structure, a benzene ring structure with a large-volume side group and a phosphorus structure, and through the organic combination of the naphthalene ring structure, the bisphenol structure and the benzene ring structure with the large-volume side group, the rigidity and the flexibility of the phosphorus-containing phenolic aldehyde curing agent can be balanced, resin carbon residues are increased, and the heat resistance of the curing agent is improved. And a promoting effect is achieved on condensed phase flame retardance. The high-heat-resistance low-dielectric multi-aromatic-ring phosphorus-containing phenolic aldehyde curing agent is applied to preparation of a composition for a copper-clad plate, the composition for the copper-clad plate is applied to preparation of the copper-clad plate, and the obtained copper-clad plate has excellent comprehensive performance: the dielectric constant is less than or equal to 3.86 and the dielectric loss is less than or equal to 0.0078 under 10GHz; the glass transition temperature is greater than or equal to 185 DEG C, the toughness of the plate is good, and the flame retardant property reaches the UL94V-0 level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic resin synthesis, and specifically is a high-heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent and a preparation method thereof, a composition for copper-clad laminates and applications thereof. Background Art

[0002] In recent years, as electronic products have become shorter, thinner, more high-performance and more multifunctional, the number of electronic components has increased, the size has decreased, the weight has decreased and the integration has continued to increase. This has put forward higher requirements for the substrate materials used in printed circuit boards that carry electronic components, in order to adapt to the development trend of increasingly high-frequency and high-speed electronic signal processing and signal transmission, and high-precision and high-integration electronic components. The requirements for substrate materials are specifically manifested in high heat resistance, excellent dielectric properties, low water absorption, good processability, etc.

[0003] Among the existing printed circuit board substrates, epoxy resin is widely used due to its good processability and comprehensive performance. However, epoxy resin is flammable and cannot meet the development needs of halogen-free flame-retardant copper-clad laminates. In the prior art, phosphorus-containing phenolic curing agent is one of the important ways to achieve halogen-free flame retardant properties for copper-clad laminates. Patent CN 117820579 A discloses a phosphorus-containing phenolic resin curing agent for copper-clad laminates, which can make the copper-clad laminate reach UL94 V0 flame retardant level at a low phosphorus content of 8.0-8.5%, and the glass transition temperature of the copper-clad laminate is about 161°C. However, as the copper-clad laminate develops towards high frequency, high speed and high integration, its heat resistance is not enough to support its use in higher heat-resistant application scenarios, and the catalyst is not treated in the reaction process. The purity of the phosphorus-containing phenolic curing agent is low, which has an adverse effect on the dielectric properties of the copper-clad laminate, and it is difficult to meet the use requirements of high-performance copper-clad laminates. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and to provide a high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent and a preparation method thereof, a composition for copper clad laminates and applications thereof, so that the prepared copper clad laminates have good dielectric properties, heat resistance, flame retardancy and toughness.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A high heat-resistant low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent comprises a naphthalene ring structure, a bisphenol structure, a benzene ring structure with a bulky side chain and a phosphorus structure.

[0007] As some possible implementation methods of the present application, the highly heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent includes the structural units shown in (I), (II) and (III) below:

[0008]

[0009] In formula (I), R1 is any one of an ether bond, a cyclohexyl group, a fluorenyl group, a phenyl group, and a biphenyl group;

[0010] R2, R4 are selected from R3, R5 are selected from methylene, In formula (II), R6 is selected from R7, R8 are selected from methylene, And R7 and R8 are not

[0011]

[0012] In formula (III), R9, R 10 Selected from methylene, And R9, R 10 Different

[0013] R 11 It is an alkyl or aralkyl group having 4 to 8 carbon atoms, including but not limited to tert-butyl, p-tert-octyl, cycloalkyl, phenyl, and o-methylphenyl.

[0014] In addition, to achieve the above object, the present invention also provides a method for preparing a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent, comprising the following steps:

[0015] S1. reacting α-naphthol, monophenol with bulky side groups, bisphenol compound and aldehyde compound under the action of alkaline catalyst to obtain hydroxymethyl compound;

[0016] S2. After the hydroxymethyl compound is subjected to a neutralization reaction, an etherification reaction, and a purification step, a dealcoholization reaction is carried out with a phosphorus-containing compound, and then the obtained product is diluted with a first solvent into a 60% to 65% resin solution, which is the high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent.

[0017] Among them, the neutralization reaction adopts an acidic compound to neutralize the alkaline catalyst, and the generated salt is removed by washing, so as to achieve the purpose of purification, thereby improving the purity of the heat-resistant low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent.

[0018] Among them, acidic compounds include but are not limited to hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, oxalic acid, glacial acetic acid, methanesulfonic acid, p-toluenesulfonic acid;

[0019] As some possible implementation methods of the present application, the bisphenol compound has a general chemical structure as shown in formula (IV):

[0020]

[0021]

[0022] In formula (IV), R 12 Selected from ether bond, cyclohexyl, fluorenyl, phenyl, biphenyl;

[0023] The monophenol with bulky side groups has a general chemical structure as shown in formula (V):

[0024]

[0025] In formula (V), R 13 It is an alkyl or aralkyl group having 4 to 8 carbon atoms, including but not limited to tert-butyl, p-tert-octyl, cycloalkyl, phenyl, and o-methylphenyl.

[0026] As some possible implementation modes of the present application, the aldehyde compound is a formaldehyde aqueous solution or paraformaldehyde.

[0027] As some possible implementation methods of the present application, the alkaline catalyst is a compound that can convert phenolic hydroxyl groups into phenolate, including but not limited to sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, trimethylamine, triethylamine;

[0028] As some possible implementation methods of the present application, the phosphorus-containing compound is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (abbreviated as DOPO) and diphenylphosphine oxide (abbreviated as DPO).

[0029] As some possible implementation methods of the present application, the first solvent is selected from any one or two of ethanol, isopropanol, n-butanol, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, acetone, butanone, and methyl isobutyl ketone.

[0030] As some possible implementation methods of the present application, the molar ratio of naphthol, monophenol with bulky side groups and bisphenol compound is (0.3-1):(0.1-0.5):1; the molar amount of aldehyde compound is 2.0-2.9 times the molar amount of phenolic hydroxyl group.

[0031] As some possible implementation methods of the present application, the hydroxymethylation reaction is carried out at 50-80°C. In order to increase the solubility of the material and the reaction effect, an appropriate amount of alcohol solvent can be added to the reaction material, such as ethanol, n-propanol, n-butanol, n-pentanol, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol, and ethylene glycol.

[0032] As some possible implementation methods of the present application, in step S2, the etherification reaction is a reaction of a hydroxymethyl compound with a primary alcohol at 70 to 110°C after neutralization; the temperature of the dealcoholization reaction is 160 to 185°C.

[0033] In addition, to achieve the above object, the present invention also provides a resin composition for copper clad laminates, comprising the following components in parts by weight:

[0034] 100 parts of multifunctional epoxy resin, 16-45 parts of active ester curing agent, 93-162 parts of high heat-resistant low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent, 0.63-7.0 parts of accelerator, and 85-133 parts of filler.

[0035] As some possible implementation methods of the present application, the multifunctional epoxy resin is a resin compound containing three or more epoxy groups, including but not limited to any one or more of phenol-type novolac epoxy resin, dicyclopentadiene phenol-type epoxy resin, bisphenol A-type novolac epoxy resin, biphenyl phenol-type epoxy resin, o-cresol-formaldehyde epoxy resin, aralkylphenol epoxy resin, phenol benzaldehyde epoxy resin, and tetraphenol ethane epoxy resin;

[0036] The active ester curing agent is a compound having an active ester group.

[0037] As some feasible embodiments of the present application, the promoter includes but is not limited to imidazoles such as 4-dimethylaminopyridine, 2-methylimidazole, 1-benzyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-ethylimidazole and 2-ethyl-4-methylimidazole; tertiary amines such as 2-(dimethylaminomethyl)phenol; and phosphines such as triphenylphosphine.

[0038] As some possible implementation methods of the present application, the filler includes but is not limited to silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide.

[0039] As some possible implementation methods of the present application, the resin composition for copper clad laminates also includes a second solvent, and the second solvent includes but is not limited to acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, and can be selected from one or two thereof.

[0040] In some possible implementation modes of the present application, the phosphorus content of the high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent is 8.0-9.2%, and the amount of the phosphorus-containing compound is determined according to the phosphorus content.

[0041] In addition, to achieve the above-mentioned purpose, the present invention also provides an application of the resin composition for copper clad laminate in the preparation of a high heat-resistant low dielectric epoxy resin-based copper clad laminate, and the preparation method of the high heat-resistant low dielectric epoxy resin-based copper clad laminate is as follows:

[0042] S1. The copper-clad laminate is configured with a resin composition to form a resin glue, and then the glass fiber is arranged in the resin glue and immersed in it and then taken out, and most of the solvent is removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C to 170°C for 1 to 10 minutes to obtain a high heat-resistant low-dielectric epoxy resin-based semi-cured sheet;

[0043] S2. Stack several layers of semi-cured sheets, attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 170°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1 to 2h, then raise the temperature to 180 to 210°C and maintain constant pressure for 4 to 8h, release the pressure and cool naturally to obtain the high heat-resistant and low dielectric epoxy resin-based copper clad laminate.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The skeleton structure of the high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent of the present application includes a large-volume side-group benzene ring structure, a naphthalene ring structure and a bisphenol structure. The large-volume side-group benzene ring structure can increase the free volume of the molecular structure, reduce the polarizability, and reduce the dielectric constant and dielectric loss of the phosphorus-containing phenolic curing agent; the naphthalene ring structure has greater rigidity and can provide good heat resistance and mechanical properties; the bisphenol compound can provide a sufficient cross-linked structure, which also helps to provide good heat resistance and mechanical properties, and the biphenyl, phenyl, cyclohexane and other structures on the bisphenol compound can also play a role in improving the dielectric properties. Through the organic combination of the three structural units, the rigidity and flexibility of the phosphorus-containing phenolic curing agent can be balanced, and the phosphorus-containing phenolic curing agent can be prevented from cracking or cracking the cured product due to excessive rigidity during the curing process. At the same time, the structures such as the naphthalene ring and bisphenol fluorene can increase the resin residual carbon, which has a promoting effect on the condensed phase flame retardancy.

[0046] (2) The resin composition for copper clad laminates of the present application comprises a high heat-resistant, low dielectric polyaromatic ring phosphorus-containing phenolic curing agent, and the resin composition for copper clad laminates has the performance characteristics of a high heat-resistant, low dielectric polyaromatic ring phosphorus-containing phenolic curing agent; the resin composition for copper clad laminates of the present application further comprises a multifunctional epoxy resin, and the multifunctional epoxy resin has excellent comprehensive performance; the resin composition for copper clad laminates of the present application further comprises an active ester curing agent, and the curing process does not produce polar hydroxyl groups, thereby further realizing the low dielectric characteristics of the resin composition.

[0047] (3) The copper clad laminate made from the resin composition for copper clad laminates of the present application has the performance characteristics of the resin composition for copper clad laminates of the present application, and the obtained copper clad laminate has excellent comprehensive performance: dielectric constant ≤3.86 and dielectric loss ≤0.0078 at 10GHz; glass transition temperature is ≥185°C, the board has good toughness, and the flame retardant performance reaches UL94 V-0 level.

[0048] (4) The preparation process of the present invention is easy to operate, and the prepared high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent and resin composition for copper-clad laminates are suitable for the field of high-performance printed circuit boards and have strong practicality. DETAILED DESCRIPTION

[0049] Part 1 Preparation of High Heat Resistant Low Dielectric Polyaromatic Phosphorus-Containing Phenolic Curing Agent (Examples 1-1 to 1-3)

[0050] Example 1-1

[0051] In a four-necked reaction bottle equipped with a mechanical stirrer, a thermometer, nitrogen, and a reflux condenser, 200 parts by mass of water, 390 parts by mass of ethanol, 42.4 parts by mass of sodium hydroxide, 172.8 parts by mass of paraformaldehyde, 50.4 parts by mass of α-naphthol, 61.8 parts by mass of p-octylphenol, and 268 parts by mass of bisphenol Z were added in sequence, and after stirring evenly, the temperature of the materials was raised to 70°C for reaction for 6 hours; after the reaction, an appropriate amount of hydrochloric acid was added to neutralize the reaction materials, and 1135 800 parts by weight of propylene glycol methyl ether are added to obtain the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent of Example 1-1, with a phosphorus content of 8.8% and a solid content of 63.1%.

[0052] Example 1-2

[0053] In a four-necked reaction bottle equipped with a mechanical stirrer, a thermometer, nitrogen, and a reflux condenser, 220 parts by mass of water, 425 parts by mass of ethanol, 56 parts by mass of sodium hydroxide, 191.7 parts by mass of paraformaldehyde, 72 parts by mass of α-naphthol, 51 parts by mass of 4-phenylphenol, and 268 parts by mass of bisphenol Z were added in sequence, and after stirring evenly, the temperature of the materials was raised to 65°C for reaction for 7 hours; after the reaction was completed, an appropriate amount of hydrochloric acid was added to neutralize the reaction materials, and 2031 parts by mass of n-butyl was added. The alcohol was reacted at 100°C for 4 hours by means of water separation and reflux using a water separator, and then an appropriate amount of water was added to maintain the temperature at 70-80°C to wash the resin, the aqueous phase was taken out from the lower layer, and the water washing operation was repeated 3 times; 849.6 parts by mass of DOPO was added to the upper resin layer, the temperature was slowly raised to 170°C and stirred for 5 hours, and 847 parts by mass of ethylene glycol methyl ether were added to obtain the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent of Example 1-1, with a phosphorus content of 8.6% and a solid content of 62.7%.

[0054] Examples 1-3

[0055] In a four-necked reaction flask equipped with a mechanical stirrer, a thermometer, nitrogen, and a reflux condenser, 150 parts by mass of water, 473 parts by mass of n-butanol, 39.2 parts by mass of sodium hydroxide, 175.8 parts by mass of paraformaldehyde, 108 parts by mass of α-naphthol, 34 parts by mass of 4-phenylphenol, and 262.8 parts by mass of bisphenol fluorene were added in sequence, and after stirring evenly, the temperature of the materials was raised to 60°C for reaction for 8 hours; after the reaction, an appropriate amount of hydrochloric acid was added to neutralize the reaction materials, and 1756 parts by mass of n-butanol were added. The reaction was carried out at 105°C for 3 hours using a water separator and reflux method, and then an appropriate amount of water was added to maintain the temperature at 70-80°C to wash the resin, the aqueous phase was taken out from the lower layer, and the water washing operation was repeated 3 times; 773.2 parts by mass of DOPO was added to the upper resin layer, the temperature was slowly raised to 175°C and stirred for 6 hours, 700 parts by mass of ethylene glycol methyl ether and 10 parts by mass of butanone were added to obtain the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent of Example 1-1, with a phosphorus content of 8.3% and a solid content of 62.5%.

[0056] Part II Preparation of High Heat Resistant Low Dielectric Epoxy Resin-Based Copper Clad Laminate (Examples 2-4)

[0057] The steps of preparing the resin composition for copper clad laminate and the high heat-resistant low dielectric epoxy resin-based copper clad laminate are as follows:

[0058] S1: 100 parts by mass of a multifunctional epoxy resin, 16 to 45 parts by mass of an active ester curing agent, 93 to 162 parts by mass of a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent, 0.63 to 7.0 parts by mass of an accelerator, 85 to 133 parts by mass of a filler, and an appropriate amount of a second solvent are uniformly mixed to form a resin adhesive, wherein the total mass of the multifunctional epoxy resin, the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent, the accelerator, and the filler accounts for 64% to 66% of the mass of the resin composition for copper clad laminates; glass fibers are arranged in the resin adhesive, immersed, and then taken out, suspended at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130° C. to 170° C. for baking for 1 to 10 minutes to obtain a high heat-resistant, low-dielectric epoxy resin-based semi-cured sheet;

[0059] S2 overlaps several layers of semi-cured sheets and attaches copper foil on both sides, places them in a vacuum hot press, raises the temperature from room temperature to 170°C at a heating rate of 3°C / min, and increases the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min. Evacuate to less than 50torr and keep pressing for 1 to 2 hours. Then raise the temperature to 180 to 210°C and keep constant pressure for 4 to 8 hours. Release the pressure and cool naturally to obtain a high heat-resistant and low-dielectric epoxy resin-based copper clad laminate.

[0060] Table 1 is a table of the proportions and performance parameters of each raw material component in Examples 2 to 4, and the units of component dosage in the table are parts by mass. In Table 1:

[0061] A1: the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent prepared in Example 1-1;

[0062] A2: the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent prepared in Example 1-2;

[0063] A3: the high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent prepared in Example 1-3;

[0064] B1: DCPD epoxy resin 7200H;

[0065] B2: biphenyl epoxy resin DC3000H;

[0066] C: Active ester curing agent DFE617;

[0067] D: 2-ethyl-4-methylimidazole;

[0068] E: silicon dioxide;

[0069] F is: butanone.

[0070] In Table 1, the relevant standards used for the technical indicators are as follows:

[0071] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;

[0072] Carbon residue: Thermogravimetric analysis (TGA) was used to test the test under a nitrogen atmosphere at a heating rate of 10°C / min.

[0073] Dielectric constant Dk and dielectric loss Df: Use SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;

[0074] Thermal delamination time T300: measured according to the method specified in 2.4.24.1 of IPC-TM-650;

[0075] Plate toughness: Use a drop hammer impact tester with a drop hammer height of 40cm and a drop hammer mass of 1kg. To evaluate toughness, the clearer, more slender and smaller the cross at the impact point is, the better the toughness of the product is, indicated by ◎; the more blurred the cross is, the larger the area is, the worse the toughness is, the greater the brittleness is, indicated by △; if the cross is between clear and blurred, the toughness of the product is average, indicated by ○;

[0076] Solder immersion resistance time with copper foil: Take a plate sample with a size of 100mm×100mm and copper foil on both sides, immerse it in 288℃ solder respectively, and take the average time without delamination and explosion;

[0077] UL 94 flame retardant performance test: measured according to UL94 vertical burning test method.

[0078] Comparative Example

[0079] 100 parts by mass of DCPD epoxy resin 7200H, 138 parts by mass of phosphorus-containing phenolic curing agent (DOW 92741, phosphorus content of about 9.0%, solid content of 57%), 34 parts by mass of active ester curing agent DFE617, 2.7 parts by mass of 2-methylimidazole, 100 parts by mass of silicon dioxide, and 168 parts by mass of butanone are prepared into a resin glue solution with a mass percentage content of 65%±1%, and then a glass fiber cloth is impregnated, and then the glass fiber cloth impregnated with the resin glue solution is baked at a temperature of 130°C to 170°C for 1 to 10 minutes to obtain a low-loss prepreg;

[0080] Stack 6 low-loss semi-cured sheets and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1 to 2h, then raise the temperature to 190°C and keep constant pressure for 5h, release the pressure and cool naturally, to obtain the copper clad laminate of comparative example 1.

[0081] Table 1:

[0082]

[0083]

[0084] It can be seen from Table 1 that the copper clad laminate prepared by using the high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent and the resin composition for copper clad laminates of the present application has good dielectric properties, heat resistance, flame retardancy and toughness. The copper clad laminate prepared by using the currently commercially available phosphorus-containing phenolic curing agent in Comparative Example 1 has poor heat resistance and dielectric properties.

[0085] Compared with the comparative example, it can be seen from Examples 2 to 4 that the high heat-resistant and low dielectric polyaromatic ring phosphorus-containing phenolic curing agent of the present application can achieve the UL94 V-0 flame retardant level of the board at a relatively low phosphorus content (<9%), can effectively increase the glass transition temperature of the board to above 185°C, improve the dielectric loss to ≤0.0078, and at the same time maintain good toughness of the board.

Claims

1. A high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent, characterized in that: The high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent comprises a naphthalene ring structure, a bisphenol structure, a benzene ring structure with a bulky side group, and a phosphorus structure.

2. A high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent according to claim 1, characterized in that: The highly heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent comprises the following structural units (Ⅰ), (Ⅱ) and (Ⅲ): In formula (I), R1 is any one of an ether bond, a cyclohexyl group, a fluorenyl group, a phenyl group, and a biphenyl group; R2, R4 are selected from R3, R5 are selected from methylene, In formula (II), R6 is selected from R7, R8 are selected from methylene, And R7 and R8 are not In formula (III), R9, R 10 Selected from methylene, And R9, R 10 Different R 11 It is an alkyl or aralkyl group having 4 to 8 carbon atoms, including but not limited to tert-butyl, p-tert-octyl, cycloalkyl, phenyl, and o-methylphenyl.

3. The method for preparing a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent according to claim 1 or 2, characterized in that: The steps include: S1. reacting α-naphthol, monophenol with bulky side groups, bisphenol compound and aldehyde compound under the action of alkaline catalyst to obtain hydroxymethyl compound; S2. After the hydroxymethyl compound is subjected to a neutralization reaction, an etherification reaction, and a purification step, a dealcoholization reaction is carried out with a phosphorus-containing compound, and then the obtained product is diluted with a first solvent into a 60% to 65% resin solution, which is the high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent.

4. The method for preparing a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent according to claim 3, characterized in that: The bisphenol compound has a general chemical structure as shown in formula (IV): In formula (IV), R 12 Selected from ether bond, cyclohexyl, fluorenyl, phenyl, biphenyl; The monophenol with bulky side groups has a general chemical structure as shown in formula (V): In formula (V), R 13 It is an alkyl or aralkyl group having 4 to 8 carbon atoms, including but not limited to tert-butyl, p-tert-octyl, cycloalkyl, phenyl, and o-methylphenyl.

5. The method for preparing a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent according to claim 3, characterized in that: The molar ratio of α-naphthol, monophenol with bulky side groups and bisphenol compound is (0.3-1):(0.1-0.5):1; the molar amount of aldehyde compound is 2.0-2.9 times the molar amount of phenolic hydroxyl group.

6. The method for preparing a high heat-resistant, low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent according to claim 3, characterized in that: In step S2, the etherification reaction is carried out by reacting the hydroxymethyl compound with the primary alcohol at 70-110° C. after neutralization; The temperature of the dealcoholization reaction is 160-185°C.

7. A resin composition for copper-clad laminates, characterized in that: It includes the following components by weight: 100 parts of multifunctional epoxy resin, 16-45 parts of active ester curing agent, 93-162 parts of high heat-resistant low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent as claimed in claim 1 or 2, 0.63-7.0 parts of accelerator, and 85-133 parts of filler.

8. A resin composition for copper-clad laminates according to claim 7, characterized in that: The multifunctional epoxy resin is a resin compound containing three or more epoxy groups, including but not limited to any one or more of phenol-type novolac epoxy resin, dicyclopentadiene phenol-type epoxy resin, bisphenol A novolac epoxy resin, biphenyl phenol-type epoxy resin, o-cresol novolac epoxy resin, aralkylphenol epoxy resin, phenol benzaldehyde epoxy resin, and tetraphenol ethane epoxy resin; The active ester curing agent is a compound having an active ester group.

9. A resin composition for copper-clad laminates according to claim 7, characterized in that: The high heat-resistant and low-dielectric polyaromatic ring phosphorus-containing phenolic curing agent has a phosphorus content of 8.0-9.2%.

10. Use of the resin composition for copper clad laminate according to any one of claims 7 to 9 in preparing high heat-resistant low dielectric epoxy resin-based copper clad laminates, characterized in that: The preparation method of the high heat-resistant low dielectric epoxy resin-based copper clad laminate is as follows: S1. The copper-clad laminate is configured with a resin composition to form a resin glue, and then the glass fiber is arranged in the resin glue and immersed in it and then taken out, and most of the solvent is removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C to 170°C for 1 to 10 minutes to obtain a high heat-resistant low-dielectric epoxy resin-based semi-cured sheet; S2. Stack several layers of semi-cured sheets, attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 170°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1 to 2h, then raise the temperature to 180 to 210°C and maintain constant pressure for 4 to 8h, release the pressure and cool naturally to obtain the high heat-resistant and low dielectric epoxy resin-based copper clad laminate.

Citation Information

Patent Citations

  • Phosphorus-containing phenolic resin curing agent for copper-clad plate and obtained copper-clad plate

    CN117820579A

  • Thermosetting resin composition as well as prepreg and laminated board manufactured by using thermosetting resin composition

    CN103304963A

  • Phenolic resin containing phosphorus, manufacture method and usage

    CN104163903A

  • Tryptamine fire retardant, synthesis and application thereof

    CN109503884A

  • Phosphorus-containing compound, epoxy resin composition, molding compound product, preparation method and application

    CN111777641A